2015
DOI: 10.1016/j.msec.2015.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anodizing parameters and heat treatment on nanotopographical features, bioactivity, and cell culture response of additively manufactured porous titanium

Abstract: Anodizing could be used for bio-functionalization of the surfaces of titanium alloys. In this study, we use anodizing for creating nanotubes on the surface of porous titanium alloy bone substitutes manufactured using selective laser melting. Different sets of anodizing parameters (voltage: 10 or 20V anodizing time: 30min to 3h) are used for anodizing porous titanium structures that were later heat treated at 500°C. The nanotopographical features are examined using electron microscopy while the bioactivity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The reported studies focused mainly on surface modification of solid and porous titanium scaffolds. For example, Yavari and coworkers [ 36 ] investigated the effect of anodizing parameters and heat treatment of SLM titanium discs and found that combination of both processes improves cell adhesion, proliferation and osteogenic differentiation. Wysocki and coworkers [ 37 ] found that chemical polishing of 3D porous titanium scaffolds fabricated by means of SLM yields lowers cell seeding efficiency but improves cell proliferation and scaffolds colonization.…”
Section: Introductionmentioning
confidence: 99%
“…The reported studies focused mainly on surface modification of solid and porous titanium scaffolds. For example, Yavari and coworkers [ 36 ] investigated the effect of anodizing parameters and heat treatment of SLM titanium discs and found that combination of both processes improves cell adhesion, proliferation and osteogenic differentiation. Wysocki and coworkers [ 37 ] found that chemical polishing of 3D porous titanium scaffolds fabricated by means of SLM yields lowers cell seeding efficiency but improves cell proliferation and scaffolds colonization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bone loss in older people due to imbalances between osteoblast and osteoclast activitymay servea role in post-fracture mortality (11,12). In addition, appropriate osteoblast calcification or bone mineralization is essential for complete bone formation (13)(14)(15). The process of bone regeneration has the potential to treat defects in bone healing in patients with osteoporosis with bone fractures or abnormalities in osteogenesis (9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…160,161 For example, in the case of the titanium alloy Ti-6Al-4V processed with SLM, a very brittle phase (i.e., a 0 ) is often formed, which reduces the fatigue life of the resulting material. 162 Heat treatments alone 76,158,[163][164][165][166][167][168][169][170] as well as in combination with high pressures (e.g., in hot isostatic pressing 157,162,171 ) and surface treatments 162 could be used to both reduce the level of the residual stresses and to improve the microstructural features of the materials processed with EBM and SLM.…”
Section: Additive Manufacturing Techniquesmentioning
confidence: 99%
“…One therefore has to rely on chemical or electrochemical techniques that are capable of reaching the internal surfaces of the porous structure. Therefore, techniques such as dipping, 209 chemical surface treatments using acid and alkali solutions, 164,210,211 anodizing, 169,212 plasma electrolytic oxidation, 145,213 and electrophoretic deposition 214,215 have been usually used for such purposes.…”
Section: Improving Bone Regeneration Performance and Osseointegrationmentioning
confidence: 99%